Spectrophotometric Determination of Cadmium(II) in Water and Soil Samples Using Schiff's Bases - Kumar, B. Natesh; Kumar, S. Himagirish; Redhi, G.G.; Jyothi, N.V.V. (Asian Journal of Chemistry, 2016)
A simple and rapid method was developed with the two novel Schiff ’s base ligands, (E)-N'-(2-hydroxy-5-nitrobenzylidene)isonicotinoylhydrazone and 2-(4-fluoro benzlideneamino)benzenothiol for monitoring the cadmium(II) in different water and soil samples. The two ligands react with cadmium(II) at pH 4.9/5.7 to form pale yellow/pale brown complexes with stoichiometric ratios of 1:1 (M:L). The complexes obeyed Beer’s law in the range of 2.0 and 2.5 mg L-1 with an excellent linearity in terms of the correlation coefficient of 0.99. The molar absorptivity and Sandell’s sensitivity of the complex systems were found to be 3.68 × 104, 4.32 × 104 L mol-1 cm-1 and 0.00298, 0.0034 μg cm-2, respectively. The limit of detection for cadmium(II) was noted as 0.042 and 0.063 μg L-1, respectively for these ligands. Furthermore, in vitro antimicrobial activities of both ligands and their complexes were successfully examined and reported.